EFFECT OF POSTURE DURING TABLET USE ON PAIN AND MUSCLE ACTIVITY IN OFFICE WORKERS - Intolo, Pattariya; Plangsiri, Komson (Journal of Sports Science and Health, 2019)
Purpose To evaluate pain and muscle activity after tablet using with a case set, on a table, and on the lap in office workers. Methods 25 participants aged 30-50 years old were recruited. Tablet use in three workstations was randomly used. At the beginning, participant was asked about pain scale. Visual analog scale (VAS) and Body pain chart were used to examine severity and location of pain immediately after tablet use for 20 minutes. EMG of Cervical erector spinae-CES, Upper trapezius-UT, Middle trapezius-MT and Wrist extensor-WT muscles were measured. Normalization of EMG signal was calculated after the processes of rectifying and smoothing EMG. Paired-t-test was used to compare severity of pain at the beginning and ending whereas One way ANOVA repeated measure was use to compare pain and EMG among three postures. Results Tablet use for 20 minutes caused neck and shoulder pain significantly(p<0.05). Participant reported neck pain 32 times and should pain 21 times in total 75 times. Severity of pain after tablet use on the lap was higher significantly (p<0.05) than tablet use with a case set (on the lap=2.97±0.63, on a case set=1.30±0.45 - Total pain scale = 10). Approximately 60%-72% of participant reported pain at least one part of body after tablet use for 20 minutes. EMG of CES during tablet use on the lap (50.53±25.44%MVC) was different significantly from tablet use on the table (66.23±26.25%MVC) and on a case set (66.98±23.05%MVC). Conclusion Tablet use for 20 minutes led to neck and shoulder pain. The highest severity of neck pain was found in Tablet use on the lap.